#### Question

Let `A =[(3,7),(2,5)] and B = [(6,8),(7,9)]`. Verify that `(AB)^(-1) = B^(-1)A^(-1)`

clickto share

#### Solution

From (1) and (2), we have:

(*AB*)^{−1} = *B*^{−1}*A*^{−1}

Hence, the given result is proved.

Is there an error in this question or solution?

#### Related Questions VIEW ALL [5]

#### Reference Material

Solution for question: Let a =[(3,7),(2,5)] and B = [(6,8),(7,9)]. Verify that (Ab)^(-1) = B^(-1)A^(-1) concept: Adjoint and Inverse of a Matrix. For the courses CBSE (Arts), CBSE (Commerce), CBSE (Science)